Efficacy and Feasibility of a Tele-health Intervention for Acute Coronary Syndrome Patients with Depression: Results of the "MoodCare" Randomized Controlled Trial. Issue 2 (26th February 2014) - O'Neil, Adrienne; Taylor, Barr; Sanderson, Kristy; Cyril, Sheila; Chan, Bianca; Hawkes, Anna L.; Hare, David L.; Jelinek, Michael; Venugopal, Kamalesh; Atherton, John J.; Amerena, John; Grigg, Leeanne; et al.
Abstract: Background: Depression is common after a cardiac event, yet there remain few approaches to management that are both effective and scalable. Purpose: We aimed to evaluate the 6-month efficacy and feasibility of a tele-health program (MoodCare) that integrates depression management into a cardiovascular disease risk reduction program for acute coronary syndrome patients with low mood. Methods: A two-arm, parallel, randomized design was used comprising 121 patients admitted to one of six hospitals for acute coronary syndrome. Results: Significant treatment effects were observed for Patient Health Questionnaire 9 (PHQ9) depression (mean difference [change] = −1.8; p =  0.025; effect size: d  = 0.36) for the overall sample, when compared with usual medical care. Results were more pronounced effects for those with a history of depression (mean difference [change] = −2.7; p =  0.043; effect size: d  = 0.65). Conclusions: MoodCare was effective for improving depression in acute coronary syndrome patients, producing effect sizes exceeding those of some face-to-face psychotherapeutic interventions and pharmacotherapy. (Trial Registration Number: ACTRN1260900038623.)